Advanced Technologies For Remote Access To Home Internet: A Review Of Potential Solutions And Their Implications - Md Ziaur Rahman (Asosiasi Riset Teknik Elektro dan Infomatika Indonesia, 2025)
With the rising demand for ubiquitous internet access, there is a growing need for technologies that allow users to remain connected to their home broadband network even when outside the house. This paper explores several proposed solutions, including advanced routers, VPNs, mobile applications, mesh networking, and hybrid cloud routers, that enable remote access to home networks. These technologies offer the potential to provide seamless, secure, and affordable connectivity, especially for individuals in rural or remote areas This innovation offers significant implications for rural internet connectivity and broader networking technology advancements. Additionally, the paper explores the societal and economic impacts of these technologies, particularly in underserved regions. By reducing dependence on expensive mobile data and providing secure, continuous internet access, these solutions can help bridge the digital divide in rural and remote areas. Improved connectivity fosters opportunities for education, remote work, and economic development, enhancing quality of life. Furthermore, advancements in hybrid cloud routers and mesh networking have the potential to drive innovation in the telecommunications industry, leading to more robust, scalable, and cost-effective networking solutions. The research underscores the need for further development and widespread implementation of these technologies to address existing internet accessibility challenges.